Advanced directions of self-control skill individualization of sports activity parameters among young combatants - Bedareva, O.; Kuzmenko, G.; Kim, T.; Levanova, E. (BIO Web of Conferences, 2020)
The functions of pedagogical control and self-control are extremely important in modern practice of sports training. They help to optimize training and competitive activity, provide achievements of different qualification athletes. The skills of self-control formation in sports activity parameters among young athletes is an important objective of a coach. In order to achieve it a coach should have a wide spectrum of special competencies. A coach should take into account individual characteristics of his athletes and organize the system of interaction, in terms of which control mechanisms, directed toward own "Self" analysis and regulation would become one of the obligatory factors of young athlete`s personality self-consciousness and the condition for his adequate inner and outer world perception. The result of the research held by the authors of the presented article became the essence, content, urgent directions of self-control skill formation in sports activity parameters among young athletes-combatants. We revealed the factors, which condition the ability to control emotional-volitional, cognitive, behavioral spheres of young athletes, taking into account the demands of sports activity and the peculiarities of information perception and processing by them.